2017
DOI: 10.1093/treephys/tpx136
|View full text |Cite
|
Sign up to set email alerts
|

Increased exposure to chilling advances the time to budburst in North American tree species

Abstract: The phenology of trees is highly susceptible to changing global temperatures. Leaf budburst advances with increasing spring temperatures, but can also be delayed when warmer winters reduce chilling exposure. Results from long-term observations show that increasing temperatures have triggered advanced budburst in the past decades, but some studies also show that budburst advance has slowed recently. Here, we conducted an experiment with five temperate deciduous tree species (Acer rubrum L., Larix laricina (Du R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 72 publications
6
45
0
Order By: Relevance
“…These results are not completely unexpected (e.g. Nanninga et al ., ) and poplars tend to have strong responses to warm temperatures, acting as ‘opportunistic’ species (Caffarra & Donnelly, ). Greater forcing temperature also strongly reduced genotypic differences in timing of bud‐break due to the steep trajectory of heat sum accumulation (Fashler & El‐Kassaby, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not completely unexpected (e.g. Nanninga et al ., ) and poplars tend to have strong responses to warm temperatures, acting as ‘opportunistic’ species (Caffarra & Donnelly, ). Greater forcing temperature also strongly reduced genotypic differences in timing of bud‐break due to the steep trajectory of heat sum accumulation (Fashler & El‐Kassaby, ).…”
Section: Discussionmentioning
confidence: 99%
“…Picea , Vitis , Quercus , Populus , Salix , Betula ) have shown that the timing of bud‐break also is strongly influenced by spring temperatures, as a certain heat sum is needed to trigger growth (Heide, ; Saxe et al ., ; Caffarra & Donnelly, ). For woody plants in temperate and boreal environments, it is critical to understand how modified temperatures stemming from climate change are expected to affect both overwintering and spring flush‐out processes (Arora et al ., ; Nanninga et al ., ). Although plasticity has broadly been observed through warmer temperatures advancing the spring date of bud‐break (Menzel & Fabian, ; Wolkovich et al ., ), the ability of different species (or populations) to respond to fluctuating conditions may be determined by the complexity of the genetic architecture underlying spring bud‐break.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally we found that increased exposure to chilling temperatures led to less forcing temperatures required prior to reproductive budburst, similar to other studies of vegetative and reproductive phenology (Harrington, Gould & St.Clair, 2010;Nanninga et al, 2017;Prevéy, Harrington & St. Clair, 2018). Thus, even if winter temperatures become warmer in the future, increasing temperatures in spring may still result in advancing budburst dates.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple studies indicate that exposure to increased chilling temperatures reduces the amount of forcing temperatures needed for reproductive budburst in spring (Harrington, Gould & St.Clair, 2010; Nanninga et al, 2017). Thus, a "possibility-line" can be modeled that predicts the amount of forcing needed for reproductive budburst based on the amount of chilling a tree has received (Harrington, Gould & St.Clair, 2010;Prevéy, Harrington & St. Clair, 2018).…”
mentioning
confidence: 99%